Investments In The Development Of Human Capital: Rate Of Return To Investments In Tertiary Education In Malaysia For The Year 2000 [LC67.6. L732 2005 f rb] [Microfiche 8542]. - Lim, Ah Kow (2005)
Pada lazimnya, orang yang mempunyai tahap pendidikan yang lebih tinggi menerima upahan yang lebih tinggi.